A Systematic Review of Dust Suppression Methods by Experiment Based on Intelligent Technology in the Coal Mines - Shanshan, Tang; Mohd Danial, Ibrahim; Andrew Ragai Henry, Rigit; Zhang, Wei; Chaokun, Wei (Engineering and Scientific Research Groups, 2024)
The mining and its transportation processes generate a substantial quantity of dust, which harms miners' health. The extended inhalation of dust particles could result in pneumoconiosis. There are numerous studies on coal mine dust removal, but only a handful of articles critically comment on it. A systematic coal mine dedusting literature review has been conducted to attempt a comprehensive and reproducible analysis. This article reviews dust suppression methods by experiment in coal mines from three aspects: chemical modification of dust removers, structural improvement of dust removers, and other factors. The review showed that independent experimental research suits dust remover's structural improvement and chemical modification. Compared to non-phytochemical modifications, phytochemical modifications are more efficient and environmentally friendly. The development of dust remover structures concentrates primarily on the nozzle structure, nozzle diameter, the number of holes, and the distance, with the nozzle diameter being of particular significance. Sometimes, tweaking the nozzle structure does not yield significant efficiency improvements. However, supersonic nozzles demonstrate high efficiency and are likely to be a key area of future research. Experiments also investigated other factors' effects on coal mines' dust removal efficacy, including ventilation system, metamorphic degree of coal, and particle diameter. This review provides the latest dust removal technology information for coal mines. Intelligent technology provides the basis for experimental research on dust removal in coal mines. The future trends of experimental research in the coal mine dust control field include intelligent and automated dust control systems, comprehensive control of multiple pollutants, application of new materials and technologies, and interdisciplinary collaboration and cross-disciplinary research.